2018
DOI: 10.1590/s0100-83582018360100097
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Desorption of Diuron, Hexazinone and Mix (Diuron + Hexazinone) in Soils With Different Attributes

Abstract: In Brazil, sugarcane is grown in large areas. Weed control in sugarcane fields is done by chemical method, since it is more efficient and less expensive. In this method, herbicides that persist in the environment for long periods are used, among which there are hexazinone and diuron, which are applied in mixtures marketed by the industry. This research evaluated the sorption and desorption of hexazinone and diuron applied alone and in mixture, in two samples of Red-Yellow Latosols (LVAG and LVAV) and a Organos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
4
1
2
Order By: Relevance
“…Mendes et al (2019) reported that the addition of bovine bone coal to the soil increased the OC content and, consequently, the sorption of hexazinone. Therefore, the results of this study reinforce the importance of soil OC in the sorption of hexazinone, as already evidenced by Oliveira Jr. et al (2001), Pang et al (2005), and Sousa et al (2018).…”
Section: Hexazinone Sorption and Soil Depthsupporting
confidence: 87%
“…Mendes et al (2019) reported that the addition of bovine bone coal to the soil increased the OC content and, consequently, the sorption of hexazinone. Therefore, the results of this study reinforce the importance of soil OC in the sorption of hexazinone, as already evidenced by Oliveira Jr. et al (2001), Pang et al (2005), and Sousa et al (2018).…”
Section: Hexazinone Sorption and Soil Depthsupporting
confidence: 87%
“…The same authors state that the sorption variations of these herbicides when mixed may be related to soil OC quality, so that being that material of origin, decomposition and structure of the organic matter of the soil can exert different influences on the sorption of herbicides. The addition of organic compounds to the soil in the research of Sousa et al (2018) may increase the retention capacity of these herbicides when mixed, differing from the present study.…”
Section: Sorption Isotherms Of Diuron Alone and Mixturecontrasting
confidence: 87%
“…Like in the present study, soils presented a variation in the CO content between 1.0 and 2.0%, indicating that in this range the CO content of the soils had little effect on the sorption of the diuron alone and in the mixture. However, for diuron alone, Giori et al (2014) found a correlation between herbicide sorption and soil OC (0.76-2.6%), as well as Sousa et al (2018), who verified a correlation of diuron sorption both alone and in mixture with hexazinone, considering a greater range of OC (1.46-27.77%). This indicates that the type of organic material present in the soil can alter the retention dynamics of the herbicides in the soil, whether isolated or mixed.…”
Section: Correlation Of Diuron (Isolated and In A Mixture) Sorption Wmentioning
confidence: 87%
See 2 more Smart Citations